2020
DOI: 10.3390/ijerph17217819
|View full text |Cite
|
Sign up to set email alerts
|

Test@Work Texts: Mobile Phone Messaging to Increase Awareness of HIV and HIV Testing in UK Construction Employees during the COVID-19 Pandemic

Abstract: Background: HIV poses a threat to global health. With effective treatment options available, education and testing strategies are essential in preventing transmission. Text messaging is an effective tool for health promotion and can be used to target higher risk populations. This study reports on the design, delivery and testing of a mobile text messaging SMS intervention for HIV prevention and awareness, aimed at adults in the construction industry and delivered during the COVID-19 pandemic. Method: Participa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…This application was a potentially useful means of providing diabetes education to patients through mass media, especially during the COVID-19 pandemic. Studies (46)(47)(48) found telephone counseling, and Middleton et al (49) found short text messages as the most useful means of informing, keeping in touch, and as a result preventing the risk of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…This application was a potentially useful means of providing diabetes education to patients through mass media, especially during the COVID-19 pandemic. Studies (46)(47)(48) found telephone counseling, and Middleton et al (49) found short text messages as the most useful means of informing, keeping in touch, and as a result preventing the risk of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, continuous use of PrEP pills when infected with HIV can lead to HIV drug resistance events (25,26), and PrEP users must be tested for HIV at frequent intervals. More web-based health promotion (e.g., text messaging) and home-based HIV-testing (e.g., oral self-tests) were practical tools for raising awareness of sexual health and HIV-testing in the United Kingdom and Africa (27,28). Thus, to flatten the curve of the COVID-19 pandemic, we suggest providing counseling and HIVST through a no-contact method to PrEP users to ensure timely knowledge of HIV serostatus and prevent HIV drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This review is critical because physical inactivity is a major risk factor for multiple diseases seen in the bariatric population, including various cardiovascular processes such as hypertension and diabetes mellitus, and has been shown to improve mental health in some populations [8,9]. Other current uses of text messaging involve increasing awareness around healthy topics and screening for various physical and mental diseases such as HIV and depression to increase early detection and begin intervention sooner [10,11]. There is also evidence that text message reminders can be used for pre-operative optimization for improved outcomes [12].…”
Section: Discussionmentioning
confidence: 99%